2011
DOI: 10.1007/s10706-011-9403-3
|View full text |Cite
|
Sign up to set email alerts
|

Undrained Cyclic and Monotonic Strength of Sand-Silt Mixtures

Abstract: In an attempt to correlate the monotonic peak strength and the cyclic strength of sand-silt mixtures over a wide range of parameters and to clarify some of the existing confusing conclusions in the literature regarding the undrained strength response of sand-silt mixtures, a series of stress controlled cyclic and strain controlled monotonic triaxial tests was carried out on sand-silt mixture specimens of 50 mm diameter and 100 mm height with varying silt content. In these experiments, various measures of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 13 publications
1
2
1
Order By: Relevance
“…4, maximum dry density increased with increase in silt content thereafter decreased; on the other hand minimum dry density decreased with increase in silt content. This minimum dry density line (decreasing with increase in silt content) was different from other researcher [19,20,33], because the minimum density tests were conducted by Water method. …”
contrasting
confidence: 67%
See 1 more Smart Citation
“…4, maximum dry density increased with increase in silt content thereafter decreased; on the other hand minimum dry density decreased with increase in silt content. This minimum dry density line (decreasing with increase in silt content) was different from other researcher [19,20,33], because the minimum density tests were conducted by Water method. …”
contrasting
confidence: 67%
“…Belkhatir et al [17,18] imply that the strength silty sand up to 50% fines content is less then that of the clean sand for constant dry density approach. Dash and Sitharam [19,20] proposed that the strength parameter initially increases till 5% silt content and thereafter decreases rapidly till around the limiting fines content (LFC) (explained in "Limiting fines content") and finally remain relatively constant for all the silt contents till even pure silt at constant relative density approach, though Karim and Alam [21] found this peak (for 5% silt content) when the specimens were prepared by air pluviation method not for moist temping method.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is shown that at a given density, CRR 15 decreases with increasing p 0 and that the effect of p 0 on CRR 15 diminishes with increasing f c . The existence of f c,th , has also been observed in previous studies on the effect of f c on the behaviour of sand with fines [38][39][40][41][42][43][44]. The f c,th is an important parameter determining the transition from the sand-dominated to the silt-dominated behaviour of mixtures and is related to their particle packing, mean diameter ratio, and separation distance as well as gradation, mineralogy, and particle shape characteristics [45].…”
Section: Liquefaction Resistancesupporting
confidence: 56%
“…Consideration of this natural trend and questions regarding silt influence on engineering behavior of sandy soils has triggered the research on silty sands in recent years. Many investigators (Kuerbis et al ,1998;Pitmanet al,1994;Lade and Yamamuro,1997;Thevanayagam, 1998;Salgado et al,2000;Thevanayagam et al ,2002;Ni et al, 2004;Murthy et al, 2007;Monkul, et al, 2011;and Dash, et al, 2011) have conducted experiment on sand with amount of silt and studied their the stress-strain behavior.…”
Section: Introductionmentioning
confidence: 99%